Wireless Networks: Characteristics and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Wireless technology has become extremely important for human life and nearly everyone carries at least one cell/mobile phone. Voice communication affects our daily lives and we are influenced by day-to-day routine. Wireless systems are being explored for numerous applications in addition to their current communication function. One can only imagine the possible innovations from an area is expanding at an unprecedented rate and offers significant future potentials. This volume is a carefully selected collection of papers that characterizes the technology and establishes its use.